2021
DOI: 10.1039/d1na00477h
|View full text |Cite
|
Sign up to set email alerts
|

Black titania an emerging photocatalyst: review highlighting the synthesis techniques and photocatalytic activity for hydrogen generation

Abstract: Schematic representations of black TiO2 preparations and its modifications to achieve benchmark hydrogen evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 120 publications
0
21
0
Order By: Relevance
“…In addition to the O L 1s peak at 529.7 eV, the deconvoluted spectrum exhibits a peak at 530.9 eV, which is typically ascribed to the oxygen vacancies (O V ), and its increased intensity may denote the abundant presence of vacancies (oxygen) in the composite. The origin of the formation of vacancies in TiO 2 could be due to the addition of NaBH 4 during the composite formation with Fe 3 O 4 and Ag . Further, the peak at 532.1 eV could be attributed to the adsorbed oxygen in the composites .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the O L 1s peak at 529.7 eV, the deconvoluted spectrum exhibits a peak at 530.9 eV, which is typically ascribed to the oxygen vacancies (O V ), and its increased intensity may denote the abundant presence of vacancies (oxygen) in the composite. The origin of the formation of vacancies in TiO 2 could be due to the addition of NaBH 4 during the composite formation with Fe 3 O 4 and Ag . Further, the peak at 532.1 eV could be attributed to the adsorbed oxygen in the composites .…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the formation of vacancies in TiO 2 could be due to the addition of NaBH 4 during the composite formation with Fe 3 O 4 and Ag. 29 Further, the peak at 532.1 eV could be attributed to the adsorbed oxygen in the composites. 30 A study by Fang et al 24 reported that the chemical reduction by NaBH 4 leads to the self-doping of Ti 3+ into the TiO 2 system via the reaction 8Ti 4+ + NaBH 4 + 2H 2 O → 8Ti 3+ + NaBO 2 + 8H + , and the emergence of Ti 3+ eventually leads to the formation of rich-oxygen defects in TiO 2 .…”
Section: Structural Investigationsmentioning
confidence: 99%
“…With increased knowledge of its electronic structure and stability under reaction conditions, additional research with the goal of producing black TiO2 under milder, less energy-intensive conditions may help further improve its activity. 326 It appears that H2 production using TiO2 based catalyst has reached its plateau and there is only a marginal increase in rates. Further work needs to be focused more on fundamental understanding using state-of-the-art facilities that bring progressive improvement in capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…With increased knowledge of its electronic structure and stability under reaction conditions, additional research with the goal of producing black TiO 2 under milder, less energy-intensive conditions may help further improve its activity. 326…”
Section: Discussionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has been considered to be one of the most encouraging photocatalysts because of its cost-effectiveness, suitable band-edge alignment, excellent chemical and thermal stability, photocorrosion resistance, strong redox ability, and less toxic nature. Meanwhile, its wide band gap (3.0–3.2 eV), quick e – /h + pair recombination, and low visible-light absorption limit TiO 2 -based photocatalysts to large-scale applications. Hence, enormous scientific achievements have been proposed to improve the charge-separation efficiency of TiO 2 mainly by incorporating other components like cocatalysts, metal oxides, and carbonaceous two-dimensional (2D) materials. Therefore, it is meaningful to obtain hybrid catalysts with high photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%